Effects of the fuel blend flow rate on engine combustion performance - Onojowho, E. E.; Asere, A. A. (Frontiers in Energy Research, 2024)
The sole aim of this study is to investigate the post-injection flow interactive effects of atomized fuel blends from an injector system of known characteristics into direct injection compression ignition engine combustion chamber and their outcomes. Attempts were made to link the interactive influence of blend mixture quality, effluence and consumption rate of fuel injection properties on frictional loss, heat liberation, combustion and volumetric efficiencies performance outcomes of the engine. This numerical-experimental dimensions' study began with computational fluid dynamics (CFD) prediction of fuel in-cylinder behavior between 225 ° CA (Crank Angle) (45 °ABDC-After Bottom Dead Center) to 360 °CA (0 ° BTDC-Before Top Dead Center) compression stroke elapsing into expansion stroke. Testo gas analyser determined the combustion efficiency. Experiment validated the CFD outcomes presented. Willans lines were applied on blends to piston frictional losses comparison. A swirl prediction maximum peak of 0.027237 at 336.15 CA for pure diesel blend (D100) at 2300 rpm and 0.066811 at 341.3 CA for pure biodiesel blend (B100) at 1800 rpm aided the mixing quality. Instantaneous velocity on sinusoidal profile and contour around swirling peaks crank angle revealed ignition activity resulting from high mixing quality. The engine possessed high efficient fuel blends burning strength on a minimum of 54.5 % at higher flow rate. Engine speed and flow rate interaction on heat liberation rate made a symmetric profile for D100 and B100. Engine energy loss on friction was minimal with D100 compared to B100 and 5 % biodiesel to 95 % diesel blend (B5).